MARKETING AND PROMOTION STRATEGIES IN INCREASING THENUMBER OF FOREIGN TOURISTS TO A THOUSAND ISLANDS - Masaji, Enggar Panggalih; Priyanto, Priyanto (Journal of Indonesian Tourism and Policy Studies, 2021)
This paper discusses the strategy carried out by the Tourism Office in promoting the Thousand Islands to foreign countries increase the number of foreign tourists' visit to the Thousand Islands. The Thousand Islands as one of the leading tourism object in Jakarta must be promoted and marketed to foreign countries. This study uses qualitative research and descriptive research with data collection techniques interviews and observations. The results of this study are to suggest and recommend other ways to promote the Thousand Islands to foreign countries and to see how the Thousand Islands itself in welcoming foreign tourists who visit the Thousand Islands. Based on the research results, the tourism office has promoted 4 pillars. There are 4 pillars of tourism promotion carried out by the Tourism Office, namely, famtrips, overseas events, sales missions, and festival participation. In addition to the promotion concept carried out by the Tourism Office, there was also the development of a marketing concept, namely the 4Ps (product, price, place, and promotion).